Staged lateral⁃posterior lumbar interbody fusion for degenerative spinal deformity - LIU Zhen‐lei; WANG Kai; LI Kang; ZHANG Lei; JIAN Feng‐zeng; WU Hao (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To evaluate the efficacy and safety of a staged lateral ⁃ posterior lumbar interbody fusion in the treatment of degenerative spinal deformity (DSD). Methods A retrospective analysis was performed on 22 patients with degenerative spinal deformity who underwent staged lateral ⁃ posterior surgery at Xuanwu Hospital, Capital Medical University from December 2021 to June 2022. The first stage involved lateral surgery, while the second stage consisted of posterior osteotomy combined with internal fixation. Pain severity was assessed by Visual Analog Scales (VAS), and disability was evaluated by Oswestry Disability Index (ODI). Radiographic measurements included the coronal balance distance (CBD), Cobb angle, sagittal vertical axis (SVA), lumbar lordosis (LL), pelvic incidence (PI), pelvic incidence and lumbar lordosis (PI ⁃LL) and pelvic tilt (PT). Results Compared with preoperation, the VAS score of low back pain (Z = 4.107, P = 0.000), the VAS score of leg pain (Z = 3.669, P = 0.000) and the ODI (Z = 4.107, P = 0.000) were decreased at the last follow ⁃ up. After staged lateral ⁃ posterior surgery, Cobb angle (χ2 = 40.364, P = 0.000), SVA (χ2 = 22.455, P = 0.000), LL (χ2 = 26.329, P = 0.000), PI ⁃LL (χ2 = 26.329, P = 0.000), PT (χ2 = 12.091, P = 0.002) improved. Compared with preoperation, Cobb angle (Z = 2.714, P = 0.000), LL (Z = 3.844, P = 0.000), PI ⁃ LL (Z = 3.844, P = 0.000), PT (Z = 2.563, P = 0.010) decreased after lateral surgery, while Cobb angle (Z = 6.332, P = 0.000), SVA (Z = 4.673, P = 0.000), LL (Z = 4.749, P = 0.000), PI ⁃LL (Z = 4.749, P = 0.000), PT (Z = 3.317, P = 0.001) decrease after posterior surgery. Compared with the lateral surgery, only Cobb angle (Z = 3.618, P = 0.000) and SVA (Z = 3.015, P = 0.000) decreased after the posterior surgery. Proximal junction failure (PJF) occurred in 2 patients (9.09%) one year after surgery, and interbody fusion sink occurred in 4 patients (18.18%) 2 years after surgery. Conclusions The staged lateral ⁃ posterior lumbar interbody fusion demonstrated good efficacy in improving clinical symptoms and restoring spinal balance in patients with degenerative spinal deformity. However, the long ⁃ term stability and safety of the procedure require further validation through large⁃scale cohort studies.